Muscle MRI Findings in Childhood/Adult Onset Pompe Disease Correlate with Muscle Function. - Sebastián Figueroa-Bonaparte; Sonia Segovia; Jaume Llauger; Izaskun Belmonte; Irene Pedrosa; Aída Alejaldre; Mercè Mayos; Guillermo Suárez-Cuartín; Eduard Gallardo; Isabel Illa; Jordi Díaz-Manera; Spanish Pompe Study Group (PLoS ONE, 2016)
Enzyme replacement therapy has shown to be effective for childhood/adult onset Pompe disease (AOPD). The discovery of biomarkers useful for monitoring disease progression is one of the priority research topics in Pompe disease. Muscle MRI could be one possible test but the correlation between muscle MRI and muscle strength and function has been only partially addressed so far.We studied 34 AOPD patients using functional scales (Manual Research Council scale, hand held myometry, 6 minutes walking test, timed to up and go test, time to climb up and down 4 steps, time to walk 10 meters and Motor Function Measure 20 Scale), respiratory tests (Forced Vital Capacity seated and lying, Maximun Inspiratory Pressure and Maximum Expiratory Pressure), daily live activities scales (Activlim) and quality of life scales (Short Form-36 and Individualized Neuromuscular Quality of Life questionnaire). We performed a whole body muscle MRI using T1w and 3-point Dixon imaging centered on thighs and lower trunk region.T1w whole body muscle MRI showed a homogeneous pattern of muscle involvement that could also be found in pre-symptomatic individuals. We found a strong correlation between muscle strength, muscle functional scales and the degree of muscle fatty replacement in muscle MRI analyzed using T1w and 3-point Dixon imaging studies. Moreover, muscle MRI detected mild degree of fatty replacement in paraspinal muscles in pre-symptomatic patients.Based on our findings, we consider that muscle MRI correlates with muscle function in patients with AOPD and could be useful for diagnosis and follow-up in pre-symptomatic and symptomatic patients under treatment.Muscle MRI correlates with muscle function in patients with AOPD and could be useful to follow-up patients in daily clinic.